Pengaruh Persepsi Kebermanfaatan, Kepercayaan serta Persepsi Risiko pada Review Online terhadap Niat Membeli di Tiktok Shop - M. Daffa Ilhamsyah; Yuniarti Fihartini; Angga Febrian (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
The purpose of this study is to analyze the influence of perceived usefulness, trust, and perceived risk in online reviews on consumers’ purchase intention on TikTok Shop. The background of this research is based on the increasing role of social commerce platforms in shaping purchasing decisions, where online reviews become a crucial factor in building trust and influencing risk perceptions. This study uses a quantitative approach with a causal research design, and the data were collected through questionnaires distributed to respondents who actively use TikTok Shop in Indonesia. To test the relationships among variables, SPSS software was employed for data analysis. The findings show that perceived usefulness, trust, and perceived risk have a significant positive effect on purchase intention, indicating that online reviews play a crucial role in consumers’ purchasing decisions. This study contributes theoretically by extending the Technology Acceptance Model (TAM) framework in the context of social commerce and also provides practical implications for businesses in designing digital marketing strategies by emphasizing the authenticity of reviews, strengthening consumer trust, and managing transaction risks.